On the Persistent Shape and Coherence of Pulsating Auroral Patches. Issue 5 (21st May 2018) - Humberset, B. K.; Gjerloev, J. W.; Mann, I. R.; Michell, R. G.; Samara, M.
Abstract: The pulsating aurora covers a broad range of fluctuating shapes that are poorly characterized. The purpose of this paper is therefore to provide objective and quantitative measures of the extent to which pulsating auroral patches maintain their shape, drift and fluctuate in a coherent fashion. We present results from a careful analysis of pulsating auroral patches using all‐sky cameras. We have identified four well‐defined individual patches that we follow in the patch frame of reference. In this way we avoid the space‐time ambiguity which complicates rocket and satellite measurements. We find that the shape of the patches is remarkably persistent with 85–100% of the patch being repeated for 4.5–8.5 min. Each of the three largest patches has a temporal correlation with a negative dependence on distance, and thus does not fluctuate in a coherent fashion. A time‐delayed response within the patches indicates that the so‐called streaming mode might explain the incoherency. The patches appear to drift differently from the SuperDARN‐determined E → × B → convection velocity. However, in a nonrotating reference frame the patches drift with 230–287 m/s in a north eastward direction, which is what typically could be expected for the convection return flow. Key Points: The shapes of the patches are remarkably persistent over periods of 4.5–8.5 min Only one of four patches fluctuates in a coherent fashion The patches appear to drift differently from the SuperDARN‐determined ExB velocity